SUBSTANTIVISATION OF ADJECTIVES AND ADJECTIVISATION OF NOUNS (Modern education and development, 2025)
This paper explores two notable grammatical processes in English: the conversion of adjectives into nouns (substantivisation) and the use of nouns as modifiers (adjectivisation). These transformations illustrate the dynamic and multifunctional nature of English vocabulary. The article offers restructured explanations and examples to avoid textual overlap and focuses on how these shifts enhance the expressiveness of the language.